BIM-based steel reinforcing bar detail construction design and picking optimization. (March 2023) - Lien, Li-Chuan; Dolgorsuren, Unurjargal
Highlights: The SRB crash nodes problems classified into four crash nodes classification and proposed a BIM-based SRB designing process. Traditional SRB engineering is a labor-intensive project, often accompanied by the quality of SRB construction and the waste of material. At present, information technology is undergoing a revolution. With the rise and optimization of Building Information Modeling (BIM) technology and the continuous improvement of artificial intelligence-based optimization algorithms, new solutions have been put forward to solve these traditional SRB engineering problems. Abstract: Steel reinforcing bar (SRB) engineering is a very professional, complex, massive, and neglected project, which affects the structural performance and cost of building. Traditional SRB engineering is a labor-intensive project, often accompanied by the quality of SRB construction and the waste of material. At present, information technology is undergoing a revolution. With the rise and optimization of Building Information Modeling (BIM) technology and the continuous improvement of artificial intelligence-based optimization algorithms, new solutions have been put forward to solve these traditional SRB engineering problems. This study combines two different fields of BIM and optimization algorithms to establish a process of BIM-based SRB detail construction design and picking optimization that provides a reference for traditional SRB engineering. It is also an exploration and application of BIM technology to practical engineering. This study classified and analyzed the SRB crash nodes problems classified into four crash nodes classification and proposed a BIM-based SRB designing process. For the problem of the SRB connection position, a general segmental formula for SRB (for example, Longitudinal SRB on columns and beams) was studied, and a set of processes was established to determine the unknowns of the segment formula to locate the connection position of SRB. Besides, this study utilizes BIM's coherent information transfer and visualization technologies that select Revit software to create new information such as "SRB shape family, " "component family, " "annotated family, " and so on. The application of BIM in SRB is carried out through the transfer, transformation, and expression of information in the forms of SRB design drawings, SRB processing schedules, SRB construction schedules, and SRB construction partition charts, and so on. in addition, the problem of one-dimensional blanking of single-size and multiple-size raw materials is discussed with the minimum number of SRB consumed as the objective function. The commonly used classical solution method is analyzed in detail, and Particle Bee Algorithm (PBA) was introduced. Through calculation and comparison of examples, the performance of PBA on the SRB problem was evaluated. The study preliminary proposed a BIM based on SRB detail construction design and picking optimization and secondary development system by a particle engineering project. The results showed that this study had a certain reference contribution for the SRB detail construction design and picking optimization.